Steel plate, member and manufacturing method thereof
A steel composition and heat treatment process address the trade-off between ductility and chemical conversion properties in high-strength steel sheets, achieving enhanced tensile strength, ductility, and chemical conversion treatability for complex automotive parts.
Patent Information
- Application Number
- JP2024542203
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-03-31
- Filing Date
- 2024-03-21
- Publication Date
- 2025-01-22
- Estimated Expiration
- 2044-03-21
AI Technical Summary
Existing high-strength steel sheets face a trade-off between ductility, hole expandability, and chemical conversion treatability, particularly when high silicon content is used to enhance ductility, leading to deteriorated chemical conversion properties and processability issues.
A steel composition with specific alloying elements (C: 0.05-0.25%, Si: 0.30-1.50%, Mn: 1.5-4.5%, P: 0.005-0.050%, S: 0.01% or less, sol.Al: less than 1.0%, N: less than 0.015%, Ti: 0.005-1.000%, B: 0.001-0.0030%) and controlled microstructure, along with a heat treatment process involving annealing and controlled cooling rates, to achieve a balance of tensile strength, ductility, and chemical conversion properties.
The solution results in a steel plate with tensile strength of 780 MPa or more, exhibiting excellent ductility, hole expandability, and chemical conversion treatability, enabling the production of complex-shaped automotive parts with reduced material costs and improved formability.
Smart Images

Figure 0007619534000006 
Figure 0007619534000007 
Figure 0007619534000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a steel sheet, a member, and a method for producing the same which are suitable for press-molded products having complex shapes that are used through a press molding process in automobiles, home appliances, etc. and have excellent chemical conversion treatability. [Background technology]
[0002] In the context of tightening global CO2 emission regulations, there is a growing demand for lighter vehicle weights through the strengthening of automotive steel sheets, and the use of high-strength steel sheets of 590 MPa or higher is being promoted for body and seat parts, replacing the existing 440 MPa-class cold-rolled steel sheets. In general, when steel sheets are strengthened, their press formability, such as ductility and stretch flangeability, decreases, making them more susceptible to cracking during press forming and reducing the degree of freedom in shape, limiting their application to parts with simple shapes. Therefore, in order to apply high-strength steel sheets to parts with complex shapes, it is important to increase the strength of the steel sheets while maintaining or improving their formability.
[0003] In light of this background, TRIP steel, which has retained austenite (residual γ) dispersed in the microstructure of a steel sheet, has been developed as a technology for improving the ductility of steel sheets. A large amount of Si is added to TRIP steel to form residual γ in the microstructure. For example, Patent Document 1 discloses that a steel sheet having high ductility (TS×El≧21000MPa·%) and high stretch flange formability of 70% or more can be obtained by austempering (carbon distribution associated with bainite transformation) in which steel containing 0.04-0.12% C, 0.8-2.5% Si, and 0.5-2.0% Mn is annealed and then held at 300-500°C for 10-900 seconds to generate 2-10% residual γ.
[0004] On the other hand, it is known that as the Si content increases, Si concentrates on the steel sheet surface after annealing, and Si-based oxides are formed, which deteriorates the chemical conversion treatability. To address this issue, for example, Patent Document 2 discloses a method of improving the chemical conversion treatability by adding Ni to prevent Si from concentrating on the steel sheet surface. Furthermore, Patent Document 3 discloses a method for improving chemical conversion treatability by appropriately controlling the content of Mn, which concentrates on the surface together with Si, so that the Si / Mn ratio is 0.40 or less, thereby forming a Mn-Si composite oxide on the surface. Furthermore, Patent Document 4 discloses a method for improving chemical conversion treatability by directly removing Si-based oxides by pickling or brushing after annealing. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent No. 5515623 [Patent Document 2] Patent No. 2951480 [Patent Document 3] Patent No. 3889768 [Patent Document 4] JP 2003-201538 A Summary of the Invention [Problem to be solved by the invention]
[0006] As described above, the addition of Si is effective in improving the ductility of high-strength steel sheets, but when Si is actively used to ensure high workability, there is a trade-off between the Si content and the phosphatability of the steel sheet. The methods disclosed in Patent Documents 2 and 4 are effective methods for improving the phosphatability of steels with a high Si content, but there has been a demand for the establishment of other techniques that adjust the alloying elements to be contained, annealing conditions, etc. Furthermore, the inventors' investigations revealed that even the method disclosed in Patent Document 3 does not necessarily ensure good chemical conversion treatability, and that when the steel contains a certain amount of B, the concentration of Si on the steel sheet surface is promoted, resulting in deterioration of chemical conversion treatability. As described above, the above-mentioned techniques are not yet sufficient as techniques for producing high-strength steel sheets having excellent ductility and chemical conversion treatability, as well as hole expandability.
[0007] The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide a steel plate, a member, and a manufacturing method thereof, which have excellent ductility, hole expandability, and chemical conversion treatability and have a tensile strength of 780 MPa or more.
[0008] Here, the tensile strength refers to the tensile strength (TS) obtained in accordance with JIS Z2241 (2011).
[0009] Moreover, excellent ductility means that the total elongation EL obtained in accordance with JIS Z2241 (2011) satisfies any one of the following (A) to (C). (A) TS: 780MPa or more but less than 980MPa, EL: 16.0% or more, (B) TS: 980 MPa or more but less than 1180 MPa, EL: 14.0% or more, (C) TS: 1180MPa or more, EL: 12.0% or more
[0010] In addition, "excellent hole expandability" means that the hole expansion ratio λ(%) (={(d-d0) / d0}×100) obtained by a hole expansion test conforming to the JFST1001 regulations is 30% or more in order to ensure the hole expandability required for practical use.
[0011] In addition, excellent chemical conversion treatability means that after degreasing (treatment temperature: 40°C, treatment time: 120 seconds, spray degreasing, degreaser: FC-E2011 manufactured by Nippon Parkerizing Co., Ltd.) and surface conditioning (pH 9.5, treatment temperature: room temperature, treatment time: 20 seconds, surface conditioner: PL-X manufactured by Nippon Parkerizing Co., Ltd.), chemical conversion treatment is then performed using a zinc phosphate chemical conversion treatment solution (chemical conversion treatment solution temperature: 35°C, treatment time: 120 seconds, chemical conversion treatment solution: Palbond PB-L3065 manufactured by Nippon Parkerizing Co., Ltd.), and the area in which the base steel is exposed is less than 10% of the total area. [Means for solving the problem]
[0012] In order to achieve the above object, the present inventors have extensively studied the effects of steel components, heat treatment conditions, and microstructures on ductility and chemical conversion treatability for various thin steel sheets having a tensile strength of 780 MPa or more. As a result, the composition contains, by mass%, C: 0.05-0.25%, Si: 0.30-1.50%, Mn: 1.5-4.5%, P: 0.005-0.050%, S: 0.01% or less, sol.Al: less than 1.0%, N: less than 0.015%, Ti: 0.005-1.000%, B: 0.0010-0.0030%, satisfies the following formulas (1) and (2), with the balance consisting of iron and unavoidable impurities, the area ratio of polygonal ferrite is 10% or more and 80% or less, the total area ratio of upper bainite, tempered martensite, and lower bainite is 10% or more and 70% or less, and the remaining It has been discovered that a high-strength cold-rolled steel sheet with excellent ductility, hole expandability and chemical conversion treatability can be obtained by setting the volume fraction of austenite (residual γ) to 3% or more and 15% or less, the area fraction of quenched martensite to 15% or less (including 0%), and further setting the steel structure to the remaining structure, and then analyzing the P emission intensity measured by glow discharge analysis from the steel sheet surface in the sheet thickness direction, the maximum P concentration [Pm] within 1 μm in the sheet thickness direction from the steel sheet surface is 0.025 mass% or more and satisfies equation (3), and further, the cumulative Si concentration within 1 μm in the sheet thickness direction from the steel sheet surface is 120 or less. [Si] / [Mn]≦0.35 Equation (1) 1000×[B] / [Mn]≦0.70...Equation (2) [Pm] / [P]≧1.5...Equation (3) In the formula (1), [Si] is the Si content (% by mass), [Mn] is the Mn content (% by mass), In formula (2), [B] is the B content (% by mass), [Mn] is the Mn content (% by mass), In formula (3), [P] is the P content (mass%).
[0013] The present invention has been made based on the above findings, and the gist of the present invention is as follows. [1] In mass percent, C: 0.05-0.25%, Si: 0.30-1.50%, Mn: 1.5-4.5%, P: 0.005-0.050%, S: 0.01% or less, Sol.Al: Less than 1.0% N: less than 0.015%, Ti: 0.005 to 1.000%, B: 0.0010~0.0030%, Contains Satisfying the following formula (1) and formula (2), The balance being iron and unavoidable impurities; Area ratio of polygonal ferrite: 10% or more and 80% or less, The total area ratio of upper bainite, tempered martensite and lower bainite is 10% or more and 70% or less, Volume fraction of retained austenite: 3% or more and 15% or less; A steel structure having an area ratio of quenched martensite of 15% or less (including 0%); having The maximum concentration of P within 1 μm from the steel sheet surface in the sheet thickness direction [Pm] is 0.025 mass% or more, and formula (3) is satisfied; Furthermore, the steel plate has an integrated concentration of Si within 1 μm from the surface in the plate thickness direction of 120 or less. [Si] / [Mn]≦0.35 Equation (1) 1000×[B] / [Mn]≦0.70...Equation (2) [Pm] / [P]≧1.5...Equation (3) In the formula (1), [Si] is the Si content (% by mass), [Mn] is the Mn content (% by mass), In formula (2), [B] is the B content (% by mass), [Mn] is the Mn content (% by mass), In formula (3), [P] is the P content (mass%). [2] The component composition further includes, in mass%, Cu: 1% or less, Ni: 1% or less, Cr: 1% or less, Mo: 0.5% or less V: 0.5% or less, Nb: 0.1% or less, Mg: 0.0050% or less, Ca: 0.0050% or less, Sn: 0.1% or less, Sb: 0.1% or less, REM: 0.0050% or less, The steel plate according to [1], containing one or more selected from the following: [3] A member made using the steel plate according to [1] or [2] above. [4] A method for producing a steel sheet, comprising the steps of: subjecting a steel slab having the composition according to [1] or [2] to hot rolling, pickling and cold rolling; and then annealing the resulting cold-rolled steel sheet; The annealing is For the cold-rolled steel sheet, in a furnace atmosphere with a dew point of -40°C or less, A c1 Point +20℃ or more A c3 a soaking temperature holding step of heating the material to a soaking temperature that is equal to or lower than the Tc point and equal to or higher than the Tc calculated by the formula (4) and holding the material at the soaking temperature for 30 to 500 s; a first cooling step of cooling the temperature range from the soaking temperature to a first cooling stop temperature of 350 to 550°C at a first average cooling rate of 2 to 50°C / s to the first cooling stop temperature; After stopping the cooling at the first cooling stop temperature, the material is allowed to remain in the temperature range of 350 to 550° C. for 10 to 60 s, A second cooling step of cooling to a second cooling stop temperature of 200 to 420°C at a second average cooling rate of 2 to 50°C / s; an isothermal holding step of holding the second cooling stop temperature for 60 to 3000 s; A method for manufacturing a steel sheet, comprising: Tc(℃)=663-1.2×exp(20 / t)×Tdp (4) Here, t is the holding time (s) at the soaking temperature, and Tdp is the dew point (° C.). [5] A method for producing a steel sheet, comprising the steps of: subjecting a steel slab having the composition according to [1] or [2] to hot rolling, pickling and cold rolling; and then annealing the resulting cold-rolled steel sheet, The annealing is For the cold-rolled steel sheet, in a furnace atmosphere with a dew point of -40°C or less, A c1 Point +20℃ or more A c3 a soaking temperature holding step of heating the material to a soaking temperature that is equal to or lower than the Tc point and equal to or higher than the Tc calculated by the formula (4) and holding the material at the soaking temperature for 30 to 500 s; a cooling step of cooling from the soaking temperature to a cooling stop temperature of 200 to 420 ° C. at an average cooling rate of 2 to 50 ° C. / s; an isothermal holding step of holding the cooling stop temperature for 60 to 3000 s; A method for manufacturing a steel sheet, comprising: Tc(℃)=663-1.2×exp(20 / t)×Tdp (4) Here, t is the holding time (s) at the soaking temperature, and Tdp is the dew point (° C.). [6] A method for manufacturing a component, comprising the step of subjecting the steel plate according to [1] or [2] above to at least one of forming and joining to form a component. Effect of the Invention
[0014] According to the present invention, it is possible to obtain a steel plate and a member which have a high strength, tensile strength TS of 780 MPa or more, and which also have excellent ductility, hole expandability and chemical conversion treatability. When the steel sheet of the present invention is applied to the frame members of an automobile body, it can be used to manufacture difficult-to-form parts of complex shapes by cold pressing, which can contribute greatly to reducing the weight of the automobile body. It is possible to reduce material costs because there is no need to use expensive alloying elements or to improve chemical conversion treatability through post-treatment after annealing. [Brief description of the drawings]
[0015] [Figure 1] FIG. 1 is a graph for explaining the maximum P concentration [Pm] of the present invention. [Diagram 2] FIG. 2 is a graph for explaining the integrated amount of Si concentration according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] The present invention will be specifically described below. Note that the present invention is not limited to the following embodiments.
[0017] (steel plate) The steel plate of the present invention contains, by mass%, C: 0.05 to 0.25%, Si: 0.30% to 1.50%, Mn: 1.5 to 4.5%, P: 0.005 to 0.050%, S: 0.01% or less, sol.Al: less than 1.0%, N: less than 0.015%, Ti: 0.005 to 1.000%, and B: 0.0010 to 0.0030%, and satisfies the following formulas (1) and (2), with the balance being iron and unavoidable impurities. The steel plate has a composition in which the area ratio of polygonal ferrite is 10% or more and 80% or less, and the total area ratio of upper bainite, tempered martensite, and lower bainite is 10% or more and 70% or less. and a steel structure in which the volume fraction of retained austenite is 3% or more and 15% or less, and the area fraction of hardened martensite is 15% or less (including 0%). When the phosphorus emission intensity is analyzed by glow discharge analysis from the surface in the sheet thickness direction, the maximum P concentration [Pm] within 1 μm in the sheet thickness direction from the steel sheet surface is 0.025 mass% or more and satisfies the following formula (3). Furthermore, the integrated Si concentration within 1 μm in the sheet thickness direction from the steel sheet surface is 120 or less. The steel sheet has a high tensile strength TS of 780 MPa or more, and is excellent in ductility, hole expandability and chemical conversion treatability. [Si] / [Mn]≦0.35 Equation (1) 1000×[B] / [Mn]≦0.70...Equation (2) [Pm] / [P]≧1.5...Equation (3) In the formula (1), [Si] is the Si content (% by mass), [Mn] is the Mn content (% by mass), In formula (2), [B] is the B content (% by mass), [Mn] is the Mn content (% by mass), In formula (3), [P] is the P content (mass%).
[0018] Hereinafter, the steel sheet of the present invention will be described in the order of chemical composition and steel structure. First, the reasons for limiting the chemical composition of the present invention will be described. In the following description, all % indicating the steel composition is mass % unless otherwise specified.
[0019] <C:0.05~0.25%> C is added from the viewpoint of securing a certain amount of retained austenite (retained γ) and improving ductility while securing a certain amount of strength through transformation strengthening. If the C content is less than 0.05%, these effects cannot be sufficiently secured. On the other hand, the upper limit of the C content is set to 0.25% due to concerns about hole expandability, which is important in press formability, and weldability, which is important in spot welding or laser welding when assembling the material into a vehicle body after forming into an automobile component. For this reason, the C content is set to 0.05 to 0.25%. The C content is preferably 0.08% or more, and more preferably 0.10% or more. The C content is preferably 0.22% or less, and more preferably 0.20% or less.
[0020] <Si:0.30~1.50%> Silicon is added from the viewpoints of strengthening ferrite to increase strength, suppressing the formation of carbides in martensite and bainite, and improving ductility by securing a certain amount of retained γ. If the Si content is less than 0.30%, these effects cannot be sufficiently secured. On the other hand, if the Si content exceeds 1.50%, good chemical conversion treatability cannot be ensured even with the production method specified in the present invention. For this reason, the Si content is set to 0.30 to 1.50%. The Si content is preferably 0.35% or more, and more preferably 0.40% or more. The Si content is preferably 1.20% or less, and more preferably 1.00% or less.
[0021] <Mn:1.5~4.5%> Mn is contained from the viewpoints of improving the hardenability of the steel sheet and promoting high strength by transformation strengthening, and suppressing the formation of carbides in bainite and promoting the formation of retained austenite contributing to ductility to improve ductility, similar to Si. To obtain these effects, the Mn content needs to be 1.5% or more. On the other hand, when the Mn content exceeds 4.5%, the bainite transformation is significantly delayed, a predetermined amount of retained austenite cannot be ensured, and the ductility decreases. Also, when the Mn content exceeds 4.5%, it becomes difficult to suppress the formation of coarse martensite by the lowering of the martensite start temperature, and the stretch flange formability (hole expansion property) deteriorates. Therefore, the Mn content is set to 1.5 - 4.5%. The Mn content is preferably 1.8% or more, more preferably 2.0% or more. Also, the Mn content is preferably 3.5% or less, more preferably 3.0% or less.
[0022] <P: 0.005 - 0.050%> P is an element that strengthens the steel. Also, by appropriately controlling the P content, a surface enrichment part of P can be generated on the surface of the steel sheet after annealing, and thus it is an element that can improve the chemical conversion treatment property. From this viewpoint, the P content is set to 0.005% or more. On the other hand, P deteriorates the spot weldability when its content is high. From this viewpoint, the P content is set to 0.050% or less. Therefore, the P content is set to 0.005 - 0.050%. The P content is preferably 0.007% or more, more preferably 0.009% or more. Also, the P content is preferably 0.040% or less, more preferably 0.030% or less.
[0023] <S: 0.01% or less> S has the effects of improving the scale peelability during hot rolling and suppressing nitriding during annealing, but it is an element that has an adverse effect on spot weldability, bendability, and hole expansion property. To reduce these adverse effects, at least the S content is set to 0.01% or less, preferably 0.0050% or less. Although it may not contain S, reducing the S content to less than 0.0001% incurs a significant cost. Therefore, from the perspective of manufacturing cost, the S content is preferably 0.0001% or more. The S content is more preferably 0.0005% or more, and even more preferably 0.0010% or more. <sol.Al: less than 1.0%> Al is contained for the purpose of deoxidation or obtaining residual γ. Although the lower limit of sol.Al is not particularly specified, for stable deoxidation, the sol.Al content is preferably 0.005% or more. On the other hand, when the sol.Al content exceeds 1.0%, a large amount of Al-based coarse inclusions increases, and the elongation flange formability (hole expansion property) deteriorates. In addition, Al is an element that deteriorates the chemical conversion treatment property of the steel sheet, and when the sol.Al content exceeds 1.0%, good chemical conversion treatment property cannot be ensured even in the present invention. Therefore, the sol.Al content is less than 1.0%. The sol.Al content is preferably 0.80% or less, and more preferably 0.06% or less.
[0024] <N: less than 0.015%> N is an element that forms nitrides such as BN, AlN, and TiN in steel and deteriorates the elongation flange formability (hole expansion property). Therefore, it is necessary to limit its content. Thus, the N content is less than 0.015%. The N content is preferably 0.010% or less, and more preferably 0.006% or less. Although it may not contain N, reducing the N content to less than 0.0001% incurs a significant cost. Therefore, from the perspective of manufacturing cost, the N content is preferably 0.0001% or more. The N content is more preferably 0.0005% or more, and even more preferably 0.001% or more.
[0025] <Ti: 0.005 - 1.000%> Ti has the effect of fixing N in steel as TiN, improving hot ductility, and improving the hardenability of B. It also has the effect of refining the structure by precipitation of TiC. To obtain these effects, the Ti content is set to 0.005% or more. It is further preferable that the Ti content is set to 0.010% or more. The Ti content is more preferably set to 0.020% or more. On the other hand, if the Ti content exceeds 1.000%, the rolling load increases and the ductility decreases due to the increased amount of precipitation strengthening. Therefore, the Ti content is set to 1.000% or less. The Ti content is preferably 0.080% or less, and more preferably 0.050% or less.
[0026] <B:0.0010~0.0030%> B is an element that improves the hardenability of steel and has the advantage of easily forming tempered martensite and / or bainite with a specified area ratio. To obtain this effect, the B content is set to 0.0010% or more. On the other hand, if the B content exceeds 0.0030%, it will concentrate on the steel sheet surface during soaking, and Mn-based oxides will coarsen, deteriorating chemical conversion treatability. Therefore, the B content is set to 0.0030% or less. The B content is preferably 0.0020% or less.
[0027] <[Si] / [Mn]≦0.35...Equation (1)> In formula (1), [Si] is the Si content (% by mass), and [Mn] is the Mn content (% by mass). [Si] / [Mn] (Si / Mn ratio) determines the component ratio of Si and Mn in the surface oxide formed during annealing. If the Si / Mn ratio exceeds 0.35 within the range of manufacturing conditions specified in the present invention, good chemical conversion treatability cannot be ensured. For this reason, [Si] / [Mn] is set to 0.35 or less. [Si] / [Mn] is preferably 0.32 or less, more preferably 0.30 or less. In addition, although there is no particular lower limit, [Si] / [Mn] is preferably 0.10 or more, more preferably 0.15 or more.
[0028] <1000 × [B] / [Mn] ≤ 0.70 ··· Formula (2)> In Formula (2), [B] is the B content (mass %), and [Mn] is the Mn content (mass %). B is an element that concentrates on the surface of the steel sheet during soaking heat retention. B promotes the formation of coarse Mn-based oxides on the steel sheet surface, creating an Mn-deficient region around it. Even when [Si] / [Mn] ≤ 0.35 is satisfied, it was newly found that B promotes the formation of Si-based oxides on the steel sheet surface, deteriorating the chemical conversion treatment property. As a result of intensive studies on this problem, regarding the contents of B and Mn, by satisfying 1000 × [B] / [Mn] ≤ 0.70, the formation of the Mn-deficient region generated during soaking heat retention can be suppressed, and the formation of Si-based oxides can be suppressed to a level where the chemical conversion treatment property does not deteriorate. Therefore, 1000 × [B] / [Mn] should be 0.70 or less. 1000 × [B] / [Mn] is preferably 0.68 or less, and more preferably 0.65 or less. Also, the lower limit is not particularly limited, but 1000 × [B] / [Mn] is preferably 0.30 or more, and more preferably 0.35 or more.
[0029] The component composition of the steel sheet in the present invention contains the above component elements as basic components, and the balance contains iron (Fe) and unavoidable impurities. Note that the component composition of the steel sheet in the present invention preferably has a component composition in which the balance consists of Fe and unavoidable impurities.
[0030] In addition to the above components, the component composition of the steel sheet of the present invention can appropriately contain one or more selected from the following as optional elements (selected elements). Cu: 1% or less, Ni: 1% or less, Cr: 1% or less, Mo: 0.5% or less, V: 0.5% or less, Nb: 0.1% or less, Mg: 0.0050% or less, Ca: 0.0050% or less, Sn: 0.1% or less, Sb: 0.1% or less, and REM: 0.0050% or less
[0031] <Cu: 1% or less> Cu improves corrosion resistance in the automotive usage environment. Also, the corrosion products of Cu have the effect of coating the steel sheet surface and suppressing hydrogen intrusion into the steel sheet. Cu is an element that is mixed in when using scrap as a raw material. By allowing the mixing of Cu, recycled materials can be utilized as raw materials, and the manufacturing cost can be reduced. From this perspective, it is preferable to contain Cu at 0.005% or more. Further, from the perspective of improving the stress corrosion cracking resistance characteristics, it is more preferable to contain Cu at 0.05% or more. The Cu content is more preferably 0.10% or more. More preferably, the Cu content is 0.25% or more, and even more preferably, it is 0.50% or more. However, if the Cu content becomes too high, it will cause the generation of surface defects. Therefore, when containing Cu, the Cu content should be 1% or less.
[0032] <Ni: 1% or less> Ni, like Cu, is an element that has the effect of improving corrosion resistance. Also, Ni has the effect of suppressing the generation of surface defects that are likely to occur when containing Cu. For this reason, it is desirable to contain Ni at 0.01% or more. The Ni content is more preferably 0.04% or more, and even more preferably 0.06% or more. However, if the Ni content becomes too high, the scale formation in the heating furnace becomes non-uniform, which instead causes the generation of surface defects. Also, it leads to an increase in cost. Therefore, when containing Ni, the Ni content should be 1% or less. Preferably, the Ni content is 0.5% or less, and more preferably 0.3% or less.
[0033] <Cr: 1% or less> Cr can be contained due to its effect of improving the hardenability of steel and its effect of suppressing carbide formation in martensite and upper / lower bainite. To obtain such effects, the Cr content is preferably 0.01% or more. The Cr content is more preferably 0.03% or more, and even more preferably 0.06% or more. However, when the Cr content is excessive, the pitting corrosion resistance deteriorates. Therefore, when Cr is contained, the Cr content should be 1% or less. The Cr content is preferably 0.75% or less, more preferably 0.50% or less. The Cr content is even more preferably 0.30% or less, and even more preferably 0.10% or less.
[0034] <Mo: 0.5% or less> Mo can be contained due to its effect of improving the hardenability of steel and its effect of suppressing carbide formation in martensite and upper / lower bainite. To obtain such effects, the Mo content is preferably 0.01% or more. The Mo content is more preferably 0.03% or more, and even more preferably 0.06% or more. More preferably, the Mo content is 0.1% or more, and even more preferably 0.2% or more. However, since Mo significantly deteriorates the chemical conversion treatment property of the cold-rolled steel sheet, when Mo is contained, the Mo content should be 0.5% or less. More preferably, the Mo content is 0.4% or less.
[0035] <V: 0.5% or less> V can be contained due to its effect of improving the hardenability of steel, its effect of suppressing carbide formation in martensite and upper / lower bainite, its effect of refining the structure, and its effect of precipitating carbides to improve the stress corrosion cracking resistance. To obtain these effects, the V content is preferably 0.003% or more. The V content is more preferably 0.005% or more, and even more preferably 0.010% or more. Even more preferably, the V content is 0.020% or more, and more preferably 0.050% or more. However, when a large amount of V is contained, the castability significantly deteriorates. Therefore, when V is contained, the V content should be 0.5% or less. Preferably, the V content is 0.3% or less, and more preferably 0.2% or less.
[0036] <Nb: 0.1% or less> Nb can be contained for the effects of refining the steel structure and increasing the strength, promoting the bainite transformation through grain refinement, improving the bendability, and enhancing the stress corrosion cracking resistance. To obtain these effects, the Nb content is preferably 0.002% or more. The Nb content is more preferably 0.004% or more, and even more preferably 0.010% or more. However, when a large amount of Nb is contained, the precipitation strengthening becomes too strong and the ductility decreases. Also, it causes an increase in the rolling load and deterioration of the castability. Therefore, when Nb is contained, the Nb content should be 0.1% or less. Preferably, the Nb content is 0.05% or less, and more preferably 0.03% or less.
[0037] <Mg: 0.0050% or less> Mg fixes O as MgO and contributes to the improvement of formability such as bendability. Therefore, the Mg content is preferably 0.0002% or more. The Mg content is more preferably 0.0004% or more, and even more preferably 0.0006% or more. The Mg content is preferably 0.0010% or more, and more preferably 0.0015% or more. On the other hand, when a large amount of Mg is added, the surface quality and bendability deteriorate. Therefore, when Mg is contained, the Mg content should be 0.0050% or less. Preferably, the Mg content is 0.0040% or less.
[0038] <Ca: 0.0050% or less> Ca fixes S as CaS and contributes to the improvement of bendability and stress corrosion cracking resistance. Therefore, the Ca content is preferably 0.0002% or more. The Ca content is more preferably 0.0005% or more, and even more preferably 0.0010% or more. The Ca content is preferably 0.0015% or more, and more preferably 0.0020% or more. On the other hand, when a large amount of Ca is added, the surface quality and bendability deteriorate. Therefore, when Ca is contained, the Ca content should be 0.0050% or less. Preferably, the Ca content is 0.0040% or less.
[0039] <Sn: Below 0.1%> Sn suppresses oxidation and nitridation of the surface layer of the steel sheet, thereby suppressing the reduction in the content of C and B in the surface layer. Due to this effect, the formation of ferrite in the surface layer of the steel sheet is suppressed, the strength is increased, and the fatigue resistance characteristics are improved. From such a perspective, the Sn content is preferably 0.003% or more. The Sn content is more preferably 0.010% or more, and even more preferably 0.015% or more. The Sn content is preferably 0.020% or more, and more preferably 0.030% or more. On the other hand, when the Sn content exceeds 0.1%, the castability deteriorates. Also, Sn segregates at the prior γ grain boundaries, and the stress corrosion cracking resistance deteriorates. Therefore, when containing Sn, the Sn content should be 0.1% or less.
[0040] <Sb: Below 0.1%> Sb suppresses oxidation and nitridation of the surface layer of the steel sheet, thereby suppressing the reduction in the content of C and B in the surface layer. Due to this effect, the formation of ferrite in the surface layer of the steel sheet is suppressed, the strength is increased, and the fatigue resistance characteristics are improved. From such a perspective, the Sb content is preferably 0.002% or more. The Sb content is more preferably 0.004% or more, and even more preferably 0.006% or more. More preferably, the Sb content is 0.008% or more, and even more preferably 0.010% or more. The Sb content is preferably 0.015% or more, and more preferably 0.030% or more. On the other hand, when the Sb content exceeds 0.1%, the castability deteriorates, and it segregates at the prior γ grain boundaries, and the stress corrosion cracking resistance deteriorates. Therefore, when containing Sb, the Sb content should be 0.1% or less.
[0041] <REM: Below 0.0050%> REM is an element that suppresses the adverse effect of sulfides on the stretch flange formability by spheroidizing the shape of sulfides, and improves the stretch flange formability. In order to obtain these effects, the REM content is preferably 0.0005% or more. The REM content is more preferably 0.0010% or more, and even more preferably 0.0020% or more. On the other hand, if the REM content exceeds 0.0050%, the effect of improving stretch flangeability becomes saturated, so if REM is contained, the REM content is set to 0.0050% or less. In the present invention, REM refers to scandium (Sc), which has atomic number 21, yttrium (Y), which has atomic number 39, and the lanthanoid elements ranging from lanthanum (La), which has atomic number 57, to lutetium (Lu), which has atomic number 71. The REM concentration in the present invention refers to the total content of one or more elements selected from the above-mentioned REM.
[0042] When the optional components are contained in amounts less than the lower limit, the optional elements contained in amounts less than the lower limit do not impair the effects of the present invention. Therefore, when the optional elements are contained in amounts less than the lower limit, the optional elements are considered to be contained as inevitable impurities.
[0043] Next, the mechanical properties of the steel sheet (cold-rolled steel sheet excellent in material stability) to which the present invention is directed will be described.
[0044] The steel sheet of the present invention has a tensile strength (TS) of 780 MPa or more. There is no particular upper limit to the tensile strength, but from the viewpoint of compatibility with other properties, the tensile strength is preferably 1300 MPa or less.
[0045] In the steel sheet of the present invention, the total elongation EL is ensured to be 16.0% or more when TS is 780 MPa or more and less than 980 MPa, 14.0% or more when TS is 980 MPa or more and less than 1180 MPa, and 12.0% or more when TS is 1180 MPa or more, thereby significantly improving the stability of press forming.
[0046] The evaluation of tensile properties is performed by taking a JIS No. 5 tensile test piece from the center position of the sheet width, and performing a tensile test (in accordance with JIS Z2241 (2011)) with N=3. Each evaluation is based on the average value of the three points. A steel sheet having a tensile strength of 780 MPa or more is considered to be a high-strength steel sheet. A steel sheet having a total elongation EL of 16.0% or more when TS is 780 MPa or more and less than 980 MPa, 14.0% or more when TS is 980 MPa or more and less than 1180 MPa, and 12.0% or more when TS is 1180 MPa or more is considered to be a steel sheet with excellent ductility. In addition, in order to ensure the hole expandability required for practical use, it is an essential condition of the present invention that the hole expansion ratio λ (%) (= {(d-d0) / d0} × 100) obtained by a hole expansion test in accordance with the provisions of JFST1001 is 30% or more.
[0047] Next, the steel structure of the steel plate of the present invention will be described.
[0048] <Area ratio of polygonal ferrite: 10% to 80%> From the viewpoint of ensuring high ductility, the area ratio of polygonal ferrite is set to 10% or more, and in order to obtain even higher ductility, the area ratio is preferably set to 20% or more. On the other hand, if the polygonal ferrite exceeds 80%, the desired strength may not be obtained, so the area ratio of polygonal ferrite is set to 80% or less, preferably 75% or less, and more preferably 70%.
[0049] <Total area ratio of upper bainite, tempered martensite and lower bainite: 10% to 70%> In order to obtain a desired strength, the total area ratio of upper bainite, tempered martensite and lower bainite is set to 10% or more, and in order to obtain even higher strength, it is preferably set to 15% or more. On the other hand, if the total area ratio of upper bainite, tempered martensite and lower bainite exceeds 70%, ductility decreases due to excessively high strength, so the area ratio is set to 70% or less, more preferably 65% or less, and further preferably 60% or less.
[0050] <Volume fraction of retained austenite (retained γ): 3% to 15%> If the volume fraction of the retained austenite is less than 3%, it may not be possible to ensure the desired ductility. From the viewpoint of ductility, the volume fraction of the retained austenite is set to 3% or more, and preferably 5% or more. On the other hand, if the volume fraction of the retained austenite exceeds 15%, the stretch flangeability (hole expandability) may decrease. Therefore, the volume fraction of the retained austenite is set to 15% or less. The volume fraction of the retained austenite is preferably 13% or less.
[0051] <Area ratio of hardened martensite: 15% or less (including 0%)> Since the hard quenched martensite structure reduces λ, its area ratio must be suppressed. In order to obtain a practically necessary λ, the area ratio of quenched martensite is set to 15% or less. In order to obtain λ more stably, the area ratio of quenched martensite is preferably 13% or less, more preferably 11% or less. The area ratio of quenched martensite may be 0% or 3% or more.
[0052] <Remaining organization> The steel structure is made up of the remaining structure except for the above. The area ratio of the remaining structure is preferably 5% or less. The remaining structure may be unrecrystallized ferrite, carbide, or pearlite. These structures may be determined by SEM observation as described later.
[0053] <The maximum P concentration [Pm] within 1 μm from the steel plate surface in the plate thickness direction is 0.025 mass% or more and formula (3) is satisfied> [Pm] / [P]≧1.5...Equation (3) In formula (3), [P] (which can also be written as [Pi]) is the P content (mass %). As a result of thorough investigation of the various elements that affect phosphatability, their surface concentration, and the type of oxides formed during annealing, it became clear that sufficient phosphatability could not be ensured even under manufacturing conditions in which no oxide formation was observed. As a result of quantitatively evaluating the maximum P concentration near the surface of steel sheets with assured phosphatability using the method described below, it was found that good phosphatability can be ensured by analyzing the P emission intensity measured from the surface in the thickness direction by GDS (glow discharge spectroscopy) when the maximum P concentration [Pm] within 1 μm in the thickness direction from the steel sheet surface is 0.025 mass% or more and the steel structure satisfies formula (3). Although the detailed mechanism is unknown, it is important that the maximum concentration of P in the surface layer is locally high relative to the steel components. Also, if this maximum concentration of P is insufficient, the shape of the chemical crystals after chemical treatment is scaly. Therefore, it is believed that the local surface concentration of P has the effect of suppressing the formation of Si-based oxides on the surface, which have a negative effect on chemical treatability. [Pm] is preferably 0.030 mass% or more, more preferably 0.035 mass% or more. Although there is no particular upper limit, [Pm] is preferably 0.100 mass% or less, more preferably 0.090 mass% or less. [Pm] / [P] is preferably 1.7 or more, more preferably 1.9 or more. Although there is no particular upper limit, [Pm] / [P] is preferably 10.0 or less, more preferably 9.0 or less.
[0054] <Cumulative amount of silicon enrichment within 1 μm from the steel plate surface in the plate thickness direction is 120 or less> In the present invention, in order to suppress the formation of Si-based oxides during soaking, 1000×[B] / [Mn] is set to 0.70 or less. In order to more reliably obtain this effect, in the present invention, the cumulative concentration amount of Si within 1 μm from the surface of the manufactured steel sheet is set to 120 or less. This ensures good chemical conversion treatability. Thus, in the present invention, the cumulative concentration amount of Si within 1 μm from the steel sheet surface is set to 120 or less. More preferably, it is 100 or less. The lower limit is not particularly limited, but is preferably 80 or more, and more preferably 90 or more.
[0055] Next, a method for measuring the steel structure will be described. The area ratios of polygonal ferrite, upper bainite, tempered martensite, lower bainite, and hardened martensite (fresh martensite) were measured by cutting out a cross section of the plate thickness parallel to the rolling direction, mirror polishing it, and then etching it with 1 vol% nital. At the 1 / 4 thickness position, an area of 25 μm x 20 μm was observed in 10 fields of view at 5,000x magnification using an SEM, and the photographed structure was quantified using image analysis. Polygonal ferrite is a relatively equiaxed ferrite with almost no carbides inside. It is the area that appears the blackest under SEM. Upper bainite is a ferrite structure with the formation of carbides or retained austenite inside that appear white under SEM. If it is difficult to distinguish between upper bainite and polygonal ferrite, the region of ferrite with an aspect ratio of ≦2.0 is classified as polygonal ferrite, and the region with an aspect ratio >2.0 is classified as upper bainite, and the area ratio is calculated. Here, the aspect ratio is calculated by determining the major axis length a at which the particle length is the longest, and the minor axis length b at the particle length when it crosses the particle the longest in the direction perpendicular to that, and a / b is the aspect ratio. Tempered martensite and lower bainite are regions with lath-shaped substructure and carbide precipitation inside when viewed under SEM. Hardened martensite (fresh martensite) is a blocky region that appears white under an SEM, with no internal substructure visible. The remaining structure is a structure that includes at least one of unrecrystallized ferrite, carbide, and pearlite, and when viewed with an SEM, the unrecrystallized ferrite is a ferrite with a black contrast that includes a deformed structure introduced by rolling, while the carbide and pearlite are a structure that can be confirmed with a white contrast. Carbide is a structure with a particle size of 1 μm or less, and pearlite is a lamellar (layer) structure, so it can be distinguished.
[0056] The volume fraction of retained austenite is determined by chemically polishing the surface layer at 1 / 4 thickness position and then performing X-ray diffraction. A Co-Kα source is used for the incident X-rays, and the volume fraction of retained austenite is calculated from the intensity ratio of the (200), (211), and (220) planes of ferrite to the (200), (220), and (311) planes of austenite. Here, since the retained austenite is randomly distributed, the volume fraction of retained austenite determined by X-ray diffraction can be taken as the area fraction of retained austenite.
[0057] The surface enrichment amounts of P and Si on and near the steel plate surface are measured by sputtering analysis in the depth direction (plate thickness direction) using a GDS (Shimadzu Corporation) under the following conditions: Ar gas pressure: 600 Pa, high frequency output: 35 W, measurement time interval: 0.1 s, measurement time: 150 s. Then, the maximum P concentration [Pm] and the cumulative enrichment amount of Si within 1 μm in the plate thickness direction from the steel plate surface are calculated using calibration curves obtained in advance using standard samples with known P and Si amounts. The cumulative amount of silicon enrichment is calculated by calculating the difference between the amount of silicon measured every 0.1 seconds within 1 μm in the thickness direction from the steel sheet surface and the average amount of silicon measured over a measurement time of 140 to 150 seconds, and integrating the measurement data within 1 μm. Note that under these measurement conditions, the measurement position d (μm) from the surface is calculated using the sputtering time ts by the formula d = ts / 1.7 (μm). In the present invention, as shown in FIG. 1, the highest P intensity value during the above-mentioned 150 s measurement time is converted into mass% using a calibration curve and defined as the maximum concentration ([Pm]). The method of conversion to mass% involves determining the correlation between the intensity of P element obtained by GDS and the amount of P in data obtained by measuring a standard material having a known amount of P under the same conditions, and converting the measured intensity of P in the examples to a concentration. In Fig. 1, Pi is the P content (mass%) in the steel sheet. The cumulative amount of Si enrichment was calculated by converting the measurement time (s) shown in Figure 2(a) by 1.7 to the depth position (μm), and then integrating the difference between the average bulk concentration (see the dashed line in Figure 2(b)) and the Si concentration (mass%) at each depth position (see the shaded area in Figure 2(b)).
[0058] (Method of manufacturing steel sheets) Next, a method for producing a steel sheet according to the present invention will be described. First Embodiment The method for producing a steel sheet according to the first embodiment of the present invention is a method for producing a steel sheet, which comprises hot rolling, pickling and cold rolling a steel slab having the above-mentioned composition, and then annealing the obtained cold-rolled steel sheet. The annealing is performed in a furnace atmosphere having a dew point of −40° C. or less, by subjecting the cold-rolled steel sheet to a c1 Point +20℃ or more A c3 a soaking temperature holding step of heating the steel sheet to a soaking temperature that is equal to or lower than the soaking point and equal to or higher than Tc calculated by formula (4) and holding the steel sheet at the soaking temperature for 30 to 500 s; a first cooling step of cooling the steel sheet to the first cooling stop temperature at a first average cooling rate of 2 to 50°C / s in a temperature range from the soaking temperature to a first cooling stop temperature of 350 to 550°C; a second cooling step of stopping the cooling at the first cooling stop temperature, retaining the steel sheet in a temperature range of 350 to 550°C for 10 to 60 s, and then cooling the steel sheet to a second cooling stop temperature of 200 to 420°C at a second average cooling rate of 2 to 50°C / s; and an isothermal holding step of holding the steel sheet at the second cooling stop temperature for 60 to 3,000 s. Tc(℃)=663-1.2×exp(20 / t)×Tdp...Equation (4) Here, t is the holding time at the above-mentioned soaking temperature (soaking holding time) (s), and Tdp is the dew point (° C.).
[0059] <Hot rolling> Methods for hot rolling steel slabs include a method of rolling the slab after heating it, a method of directly rolling the slab after continuous casting without heating it, and a method of rolling the slab after continuous casting after subjecting it to a short-term heat treatment. Hot rolling may be carried out according to a conventional method, and for example, the slab heating temperature may be 1100°C or higher. The slab heating temperature may be 1300°C or lower. The soaking temperature may be 20 min or higher. The soaking temperature may be 300 min or lower. The finish rolling temperature may be A r3 The finishing rolling temperature should be above the transformation point. r3 The coiling temperature may be set to the transformation point +200°C or lower. The coiling temperature may be set to 400°C or higher. The coiling temperature may be set to 720°C or lower. The coiling temperature is preferably controlled from the viewpoint of suppressing thickness fluctuation and stably ensuring high strength. Specifically, the coiling temperature is preferably set to 430°C or higher. The coiling temperature is preferably set to 530°C or lower. In addition, A r3 The transformation point can be calculated from the composition of the steel sheet and the following empirical formula (A). A r3 Point (℃)=910-310×[C]-80×[Mn]-20×[Cu]-15×[Cr]-55×[Ni]-80×[Mo]...Formula (A) (In the above formula, [M] is the content (mass%) of element M in the steel slab, and the value of an element that is not contained is zero (0).)
[0060] <Pickling> The pickling may be carried out in a conventional manner.
[0061] <Cold rolling> Cold rolling may be performed according to a conventional method, and the rolling ratio (cumulative rolling ratio) may be 30% or more. The rolling ratio (cumulative rolling ratio) may be 85% or less. The rolling ratio is preferably controlled from the viewpoint of stably securing high strength and reducing anisotropy. Specifically, the rolling ratio is preferably 35% or more. When the rolling load is high, softening annealing treatment can be performed at 450 to 730°C in a CAL (continuous annealing line) or BAF (box annealing furnace).
[0062] <Annealing> A cold-rolled steel sheet manufactured according to a conventional method is annealed under the following conditions. The annealing equipment is not particularly limited, but it is preferable to carry out the annealing in a continuous annealing line (CAL) from the viewpoints of productivity and ensuring the desired heating rate and cooling rate.
[0063] [Soaking process: In a furnace atmosphere with a dew point of -40°C or less, c1 Point +20℃ or more A c3 Heat to a temperature below the Tc point and above Tc, and hold at the temperature for 30 to 500 seconds. The dew point affects the formation of oxides on the steel sheet surface during annealing, and if the dew point exceeds -40°C, the amount of oxides formed on the steel sheet surface increases excessively, deteriorating the chemical conversion treatability. For this reason, the dew point is set to -40°C or lower. Although there is no particular lower limit, the dew point is preferably -70°C or higher, and more preferably -60°C or higher.
[0064] The steel sheet obtained by the present invention contains a soft ferrite structure, which improves ductility. Therefore, the soaking temperature is set at the A temperature where ferrite is formed. c1 Point +20℃ or more A c3 Points or less.
[0065] Furthermore, by setting the soaking temperature to Tc (°C) or higher, the amount of P concentrated at the P surface concentrated portion formed on the steel sheet surface can be ensured to be within the range specified in the present invention. Tc is calculated from the dew point and the soaking holding time in formula (4). Tc(℃)=663-1.2×exp(20 / t)×Tdp...Equation (4) Here, t is the holding time (s) at the soaking temperature, and Tdp is the dew point (°C). If the soaking temperature is less than Tc (℃), the desired amount of P on the surface cannot be secured, and the phosphatability deteriorates. Therefore, in a furnace atmosphere with a dew point of -40℃ or less, the soaking temperature is set to A c1 Point +20℃ or more A c3 The temperature must be below this point and above Tc (℃).
[0066] Furthermore, if the time for holding at the soaking temperature (soaking holding time) is less than 30 seconds, austenite will not be sufficiently formed at the soaking temperature, resulting in an increase in polygonal ferrite, and the desired total area ratio of upper bainite, tempered martensite, and lower bainite will not be obtained, making it possible that the desired strength cannot be obtained or that the desired ductility cannot be secured due to insufficient retained austenite. On the other hand, if the time for holding at the above-mentioned soaking temperature (soaking holding time) exceeds 500 seconds, the structure will become significantly coarse, and the desired strength may not be ensured, and the desired ductility may not be obtained. Therefore, the time for which the steel sheet is held at the annealing temperature (soaking time) is set to 30 to 500 seconds. The time for which the material is held at the soaking temperature (soaking time) is preferably 60 seconds or more, more preferably 100 seconds or more, and is preferably 400 seconds or less, more preferably 300 seconds or less.
[0067] In addition, the above A c1 and A c3 is obtained from the empirical formulas (5) and (6) below. c1 and A c3 can be used. A c1 =723+22×[C]-18×[Si]+17×[Cr]+4.5×[Mo]+16×[V]...Formula (5) A c3 =910-203×([C]) 1 / 2 +44.7×[Si]-30×[Mn]+700×[P]+400×[sol.Al]-20×[Cu]+31.5×[Mo]+104×[V]+400×[Ti]...Formula (6) Here, [M] is the mass percentage of each element.
[0068] [First cooling step: Cooling from the soaking temperature to the first cooling stop temperature of 350-550°C at a first average cooling rate of 2-50°C / s] A c1 Point +20℃ or more Ac3 After being held at a soaking temperature that is equal to or lower than the soaking point and equal to or higher than Tc (after the soaking step), the material is cooled in a temperature range from the soaking temperature to a first cooling stop temperature of 350 to 550° C. at a first average cooling rate of 2 to 50° C. / s. If the first average cooling rate is less than 2° C. / s, the ferrite transformation during cooling proceeds excessively and the desired amount of polygonal ferrite cannot be obtained, so the first average cooling rate is set to 2° C. / s or more, and preferably 5° C. / s or more. On the other hand, if the first average cooling rate is too high, the sheet shape deteriorates, so the first average cooling rate is set to 50° C. / s or less. The first average cooling rate is preferably 40° C. / s or less, and more preferably less than 30° C. / s. Here, the first average cooling rate is "(soaking temperature (°C)-first cooling stop temperature (°C)) / cooling time (seconds) from the soaking temperature to the first cooling stop temperature".
[0069] [Second cooling step (1): Retention at 350-550℃ for 10s to 60s] At temperatures below the first cooling stop temperature and in the temperature range of 350°C to 550°C (dwell temperature), upper bainite can be formed, a predetermined amount of retained austenite can be obtained, and the desired ductility can be obtained. Bainite transformation has an incubation period, and in order to obtain the desired amount of bainite, the material must be held at that temperature for a certain period of time. If the holding temperature range including the holding start temperature (=first cooling stop temperature) and holding end temperature is outside the range of 350 to 550°C, and / or if the holding time (hereinafter also referred to as holding time) is less than 10 s, the desired amount of bainite cannot be obtained, the formation of retained austenite is suppressed, and the desired ductility cannot be obtained. On the other hand, if the holding time exceeds 60 s, the concentration of C from bainite to the blocky untransformed γ progresses, leading to an increase in the amount of remaining blocky quenched martensite structure or an excessive increase in retained austenite, which may cause a decrease in λ. Therefore, the holding time is set to 10 s or more and 60 s or less. This holding time is preferably 20 s or more. Moreover, this holding time is preferably 50 s or less. Depending on the desired properties, the second cooling step (1) can be omitted. In that case,c1 Above +20℃A c3 After the soaking temperature is heated to a soaking temperature of Tc or higher and maintained at the soaking temperature for 30 to 500 s, the second cooling step (2) may be performed. A manufacturing method in which the second cooling step (1) is omitted will be described in the second embodiment described later.
[0070] [Second cooling step (2): Cool to a second cooling stop temperature of 200 to 420°C at a second average cooling rate of 2 to 50°C / s] After the above-mentioned retention, it is necessary to cool quickly so that the bainite transformation does not proceed excessively. If the average cooling rate (second average cooling rate) in the temperature range from the retention end temperature to the second cooling stop temperature of 200°C to 420°C is less than 2°C / s, the bainite transformation may proceed excessively, resulting in an excessive increase in retained austenite, or the desired amount of martensite may not be secured, resulting in a decrease in strength. In addition, if the second average cooling rate is less than 2°C / s, the desired ductility and hole expandability may not be obtained. Therefore, the second average cooling rate in the temperature range from the retention end temperature to the second cooling stop temperature of 200° C. or more and 420° C. or less is set to 2° C. / s or more. The second average cooling rate is preferably 5° C. / s or more, and more preferably 8° C. / s or more. If the cooling rate in this temperature range is too high, the sheet shape deteriorates, so the cooling rate in this temperature range (second average cooling rate) is set to 50° C. / s or less, preferably 40° C. / s or less. If the second cooling stop temperature exceeds 420°C, the area ratio of tempered martensite or lower bainite will not be the specified value, and the area ratio of quenched martensite after annealing will increase, so that the residual γ cannot be secured and ductility may deteriorate. Also, hole expandability may deteriorate. For this reason, the second cooling stop temperature is set to 420°C or less. The second cooling stop temperature is preferably 400°C or less. On the other hand, if the second cooling stop temperature is less than 200°C, the tempering effect of martensite is not sufficient, and the formation of lower bainite is suppressed, so not only does the amount of quenched martensite increase, but the concentration of C in the residual γ is suppressed, deteriorating ductility. For this reason, the second cooling stop temperature is set to 200°C or higher. Here, the second average cooling rate is "retention end temperature (°C)-second cooling stop temperature (°C) / cooling time (seconds) from the retention end temperature to the second cooling stop temperature".
[0071] [Isothermal holding process: Holding for 60~3000s at second cooling stop temperature] Holding at the second cooling stop temperature is performed from the viewpoint of adjusting the strength by tempering the martensite formed and promoting the enrichment of C in the residual γ. If the temperature is less than 60 s, the tempering is insufficient, resulting in the formation of high-strength martensite, and the enrichment of C in the residual γ is suppressed, so the desired ductility and hole expandability are not secured. On the other hand, if the holding time at the second cooling stop temperature exceeds 3000 s, the martensite is excessively tempered, and the desired strength may not be ensured. Also, if the holding time at the second cooling stop temperature exceeds 3000 s, the desired ductility may not be obtained. Therefore, the holding time at the second cooling stop temperature is set to 60 s or more and 3000 s or less. The holding time at the second cooling stop temperature is preferably 100 s or more, more preferably 150 s or more. Moreover, the holding time at the second cooling stop temperature is preferably 2500 s or less, more preferably 2000 s or less.
[0072] Second Embodiment The method for producing a steel sheet according to the second embodiment of the present invention is a method for producing a steel sheet, which comprises hot rolling, pickling and cold rolling a steel slab having the above-mentioned composition, and then annealing the obtained cold-rolled steel sheet. The annealing is performed in a furnace atmosphere having a dew point of −40° C. or less, by subjecting the cold-rolled steel sheet to a c1 Point +20℃ or more A c3a soaking temperature holding step of heating the steel sheet to a soaking temperature that is equal to or lower than the soaking point and equal to or higher than Tc calculated by formula (4) and holding the steel sheet at the soaking temperature for 30 to 500 s, a cooling step of cooling the steel sheet from the soaking temperature to a cooling stop temperature of 200 to 420°C at an average cooling rate of 2 to 50°C / s, and an isothermal holding step of holding the steel sheet at the cooling stop temperature for 60 to 3,000 s. Tc(℃)=663-1.2×exp(20 / t)×Tdp...Equation (4) Here, t is the holding time (s) at the above-mentioned soaking temperature, and Tdp is the dew point (°C).
[0073] In the second embodiment, the treatments in the soaking steps of hot rolling, pickling, cold rolling, and annealing can be performed under the same conditions as in the first embodiment. In the second embodiment, the first cooling step in the annealing of the first embodiment can be omitted. In the second embodiment, the cooling step in the annealing corresponds to the second cooling step in the annealing in the first embodiment. However, in the cooling step in this embodiment, the retention treatment in the second cooling step in the first embodiment (retention for 10 to 60 s in a temperature range of 350 to 550°C) can be omitted. In addition, the isothermal holding step in the annealing of the second embodiment can be substantially the same as the isothermal holding step in the annealing of the first embodiment, except that the second cooling stop temperature is the cooling stop temperature. In the present embodiment, the cooling step in the annealing will be mainly described below.
[0074] [Cooling process: Cool to a cooling stop temperature of 200-420°C at an average cooling rate of 2-50°C / s] After the soaking process, the steel must be cooled quickly to prevent excessive bainite transformation. If the average cooling rate in the temperature range from the soaking temperature to the second cooling stop temperature of 200°C to 420°C is less than 2°C / s, the bainite transformation may proceed excessively, the desired amount of quenched martensite may not be secured, and strength may decrease. Also, if the average cooling rate is less than 2°C / s, the desired hole expandability may not be obtained. Therefore, the average cooling rate in the temperature range from the soaking temperature to the cooling stop temperature of 200° C. or more and 420° C. or less is set to 2° C. / s or more. The average cooling rate is preferably 5° C. / s or more, and more preferably 8° C. / s or more. If the cooling rate in this temperature range is too high, the sheet shape deteriorates, so the cooling rate in this temperature range (second average cooling rate) is set to 50° C. / s or less, preferably 40° C. / s or less. If the cooling stop temperature exceeds 420°C, the area ratio of tempered martensite or lower bainite will not be the specified value, and the area ratio of quenched martensite after annealing will increase, which may result in a deterioration of hole expandability. For this reason, the cooling stop temperature is set to 420°C or less. On the other hand, if the cooling stop temperature is less than 200°C, the tempering effect of martensite is not sufficient, and not only does the amount of quenched martensite increase, but the concentration of C in the residual γ is suppressed, which may result in deterioration of ductility. For this reason, the cooling stop temperature is set to 200°C or higher. Here, the average cooling rate is "soaking temperature (°C)-cooling stop temperature (°C) / cooling time (seconds) from the soaking temperature to the cooling stop temperature".
[0075] Plate Thickness The steel sheet of the present invention preferably has a thickness of 0.5 mm or more, and more preferably has a thickness of 3.0 mm or less.
[0076] (Components and their manufacturing methods) Next, the member of the present invention and the method for producing the same will be described.
[0077] The member of the present invention is obtained by subjecting the steel plate of the present invention to at least one of forming and joining. Also, the method for producing the member of the present invention includes a step of subjecting the steel plate of the present invention to at least one of forming and joining to obtain the member.
[0078] The steel plate of the present invention has a tensile strength of 780 MPa or more, and has excellent ductility, hole expandability, and chemical conversion treatability. Therefore, the member obtained by using the steel plate of the present invention also has a tensile strength of 780 MPa or more, and has excellent ductility, hole expandability, and chemical conversion treatability. In addition, the member of the present invention can be made lighter. Therefore, the member of the present invention can be suitably used, for example, for vehicle body frame parts.
[0079] The forming process may be performed by a general processing method such as pressing, without any restrictions. The joining process may be performed by a general welding method such as spot welding or arc welding, riveting, or crimping, without any restrictions. EXAMPLES
[0080] <Example 1> A slab having the chemical composition shown in Table 1 produced by continuous casting was heated to 1200°C, with a soaking time of 200 min, a finish rolling temperature of 860°C or higher, and a coiling temperature of 550°C. After the hot rolling process, the slab was cold rolled at a rolling ratio of 50% to produce a cold-rolled steel sheet having a thickness of 1.4 mm. The cold-rolled steel sheet was treated under the annealing conditions shown in Table 2 to produce the steel sheet of the present invention and the steel sheet of the comparative example.
[0081] [Table 1]
[0082] The steel structure was measured by the following method. The measurement results are shown in Table 3. The area ratios of polygonal ferrite, upper bainite, tempered martensite, lower bainite, and hardened martensite (fresh martensite) were measured by cutting out a cross section of the plate thickness parallel to the rolling direction, mirror polishing it, and then etching it with 1 vol% nital. At the 1 / 4 thickness position, an area of 25 μm x 20 μm was observed in 10 fields of view at 5,000x magnification using an SEM, and the photographed structure was quantified using image analysis. Polygonal ferrite is a relatively equiaxed ferrite with almost no carbides inside. It is the area that appears the blackest under SEM. Upper bainite is a ferrite structure with the formation of carbides or retained austenite inside that appear white under SEM. When it was difficult to distinguish between upper bainite and polygonal ferrite, the area of ferrite with an aspect ratio of ≦2.0 was classified as polygonal ferrite, and the area with an aspect ratio of >2.0 was classified as upper bainite, and the area ratio was calculated. Here, the aspect ratio was calculated by determining the major axis length a at which the particle length is the longest, and the minor axis length b at the particle length when it crosses the particle the longest in the direction perpendicular to that, and a / b was defined as the aspect ratio. Tempered martensite and lower bainite are regions with lath-shaped substructure and carbide precipitation inside when viewed under SEM. Hardened martensite (fresh martensite) is a blocky region that appears white under an SEM, with no internal substructure visible. The remaining structure is a structure that includes at least one of unrecrystallized ferrite, carbide, and pearlite. Under SEM, unrecrystallized ferrite can be confirmed as ferrite with black contrast that includes deformed structure introduced by rolling. Carbide and pearlite are structures that can be confirmed with white contrast. Carbide is a structure with a particle size of 1 μm or less, and pearlite is a lamellar (layer) structure, so it can be distinguished.
[0083] The volume fraction of retained austenite was determined by chemical polishing at the 1 / 4 thickness position from the surface layer and X-ray diffraction. A Co-Kα source was used for the incident X-rays, and the volume fraction of retained austenite was calculated from the intensity ratio of the (200), (211), and (220) planes of ferrite to the (200), (220), and (311) planes of austenite.
[0084] JIS No. 5 tensile test pieces were taken from the obtained steel plates, and tensile tests (based on JIS Z2241 (2011)) were performed with N=3. Each evaluation was based on the average value of the three points. Steel plates with a tensile strength of 780 MPa or more were judged to have excellent strength. The total elongation EL was determined to be excellent when it was 16.0% or more for TS: 780 MPa or more, 14.0% or more for TS: 980 MPa or more, and 12.0% or more for TS: 1180 MPa or more. In addition, a hole expansion test in accordance with the JFST1001 regulations was performed with N=3, and the average of the three hole expansion ratios λ (%) (={(d-d0) / d0}×100) was set at 30% or more as the pass criterion, with a value of 30% or more being judged to indicate excellent hole expansion property. The measurement results are shown in Table 3.
[0085] The surface enrichment of P and Si on the annealed steel sheet was measured using a GDS (Shimadzu Corporation) by performing a depth-direction sputtering analysis under the conditions of Ar gas pressure: 600 Pa, high frequency output: 35 W, measurement time interval: 0.1 s, and measurement time: 150 s, and the maximum P concentration [Pm] and the cumulative enrichment of Si near the surface (within 1 μm in the sheet thickness direction from the steel sheet surface) were measured. In this measurement, calibration curves for P and Si were obtained using standard samples with various P contents from 0.005 to 0.020 mass% and standard samples with various Si contents from 1.0 to 3.0 mass%.
[0086] The annealed steel sheet was degreased and surface-conditioned, and then chemically treated using a zinc phosphate chemical treatment solution. Specifically, the chemical treatment was performed as follows: degreasing step: treatment temperature; 40°C, treatment time; 120 seconds, spray degreasing; surface conditioning step: pH 9.5, treatment temperature; room temperature, treatment time; 20 seconds; chemical treatment step: chemical treatment solution temperature; 35°C, treatment time; 120 seconds. Note that the treatment agents used in the degreasing step, surface conditioning step, and chemical treatment step, respectively, were degreaser FC-E2011, surface conditioning agent PL-X, and chemical treatment solution Palbond PB-L3065, all manufactured by Nihon Parkerizing Co., Ltd. Magnification: 1000 times, 5 visual fields (50,000 μm 2 The surface chemical structure was observed by SEM observation of the above areas, and the area where the base steel was exposed was rated as ◯ when it was less than 10% of the total area, and x when it was 10% or more. The results are shown in Table 3.
[0087] [Table 2]
[0088] [Table 3]
[0089] The examples of the present invention shown in Tables 2 and 3 were excellent in strength, ductility, hole expandability and chemical conversion treatability, whereas the comparative examples were inferior in any of these properties.
[0090] <Example 2> A slab produced by continuous casting having the composition shown in Table 1 was heated to 1200°C, and subjected to a hot rolling process in which the soaking time was 200 min, the finish rolling temperature was 860°C or higher, and the coiling temperature was 550°C. The cold-rolled steel sheet having a thickness of 1.4 mm was produced by cold rolling at a rolling ratio of 50%, and was treated under the annealing conditions shown in Table 4 to produce the steel sheet of the present invention and the steel sheet of the comparative example. The same evaluation as in Example 1 was carried out. The results are shown in Table 5.
[0091] [Table 4]
[0092] [Table 5]
[0093] The examples of the present invention shown in Tables 4 and 5 were excellent in ductility and chemical conversion treatability, whereas the comparative examples were inferior in either of these properties.
[0094] In addition, it was found that the components obtained by forming and joining the steel plates of the present invention have excellent strength, ductility, hole expandability and chemical treatability, similar to the steel plates of the present invention, because the steel plates of the present invention are excellent in strength, ductility, hole expandability and chemical treatability.
Claims
1. In mass percent, C: 0.05-0.25%, Si: 0.30-1.50%, Mn: 1.5-4.5%, P: 0.005-0.050%, S: 0.01% or less, sol. Al: less than 1.0%; N: less than 0.015%; Ti: 0.005 to 1.000%, B: 0.0010-0.0030%, Contains The following formulas (1) and (2) are satisfied, The balance being iron and unavoidable impurities; Area ratio of polygonal ferrite: 10% or more and 80% or less, Total area ratio of upper bainite, tempered martensite, and lower bainite: 10% or more and 70% or less, Volume fraction of retained austenite: 3% or more and 15% or less, Area ratio of quenched martensite: 15% or less (including 0%), A steel structure having an area ratio of the remaining structure of 5% or less; having The maximum concentration of P [Pm] within 1 μm in the sheet thickness direction from the steel sheet surface is 0.025 mass% or more, and the following formula (3) is satisfied: Furthermore, the steel sheet has an integrated concentration of Si within 1 μm from the steel sheet surface in the sheet thickness direction of 120 or less. [Si] / [Mn]≦0.35...Formula (1) 1000×[B] / [Mn]≦0.70...Formula (2) [Pm] / [P]≧1.5...Formula (3) In the formula (1), [Si] is the Si content (% by mass), [Mn] is the Mn content (% by mass), In formula (2), [B] is the B content (% by mass), [Mn] is the Mn content (% by mass), In formula (3), [P] is the P content (mass%).
2. The composition further includes, in mass%, Cu: 1% or less, Ni: 1% or less, Cr: 1% or less, Mo: 0.5% or less, V: 0.5% or less, Nb: 0.1% or less, Mg: 0.0050% or less, Ca: 0.0050% or less, Sn: 0.1% or less, Sb: 0.1% or less, REM: 0.0050% or less The steel sheet according to claim 1, containing one or more selected from the following:
3. A member made using the steel sheet according to claim 1 or 2.
4. A method for producing a steel sheet, comprising the steps of: subjecting a steel slab having the composition according to claim 1 or 2 to hot rolling, pickling and cold rolling; and then annealing the resulting cold-rolled steel sheet, The annealing is The cold-rolled steel sheet is subjected to a furnace atmosphere having a dew point of −40° C. or less, c1 Point +20℃ or more A c3 a soaking temperature holding step of heating the sample to a soaking temperature that is equal to or lower than the Tc point and equal to or higher than the Tc calculated by formula (4) and holding the sample at the soaking temperature for 30 to 500 s; A first cooling step of cooling the temperature range from the soaking temperature to a first cooling stop temperature of 350 to 550 ° C. at a first average cooling rate of 2 to 50 ° C. / s to the first cooling stop temperature; After stopping the cooling at the first cooling stop temperature, the material is allowed to stay in a temperature range of 350 to 550 ° C. for 10 to 60 s, A second cooling step of cooling to a second cooling stop temperature of 200 to 420 ° C. at a second average cooling rate of 2 to 50 ° C. / s; an isothermal holding step of holding the second cooling stop temperature for 60 to 3000 s; Including, a steel structure having an area ratio of polygonal ferrite: 10% or more and 80% or less, a total area ratio of upper bainite, tempered martensite, and lower bainite: 10% or more and 70% or less, a volume ratio of retained austenite: 3% or more and 15% or less, an area ratio of quenched martensite: 15% or less (including 0%), and an area ratio of a residual structure: 5% or less, a maximum concentration of P [Pm] within 1 μm in the plate thickness direction from the steel plate surface is 0.025 mass% or more and satisfies the following formula (3), and further, an integrated concentration amount of Si within 1 μm in the plate thickness direction from the steel plate surface is 120 or less. [Pm] / [P]≧1.5 (3) Tc (℃) = 663-1.2 x exp (20 / t) x Tdp (4) Here, in formula (3), [P] is the P content (mass%), and in formula (4), t is the retention time (s) at the soaking temperature, and Tdp is the dew point (° C.).
5. A method for producing a steel sheet, comprising the steps of: subjecting a steel slab having the composition according to claim 1 or 2 to hot rolling, pickling and cold rolling; and then annealing the resulting cold-rolled steel sheet, The annealing is The cold-rolled steel sheet is subjected to a furnace atmosphere having a dew point of −40° C. or less, c1 Point +20℃ or more A c3 a soaking temperature holding step of heating the sample to a soaking temperature that is equal to or lower than the Tc point and equal to or higher than the Tc calculated by formula (4) and holding the sample at the soaking temperature for 30 to 500 s; A cooling step of cooling from the soaking temperature to a cooling stop temperature of 200 to 420 ° C. at an average cooling rate of 2 to 50 ° C. / s; an isothermal holding step of holding the cooling stop temperature for 60 to 3000 s; Including, a steel structure having an area ratio of polygonal ferrite: 10% or more and 80% or less, a total area ratio of upper bainite, tempered martensite, and lower bainite: 10% or more and 70% or less, a volume ratio of retained austenite: 3% or more and 15% or less, an area ratio of quenched martensite: 15% or less (including 0%), and an area ratio of a residual structure: 5% or less, a maximum concentration of P [Pm] within 1 μm in the plate thickness direction from the steel plate surface is 0.025 mass% or more and satisfies the following formula (3), and further, an integrated concentration amount of Si within 1 μm in the plate thickness direction from the steel plate surface is 120 or less. [Pm] / [P]≧1.5 (3) Tc=663-1.2×exp(20 / t)×Tdp...(4) Here, in formula (3), [P] is the P content (mass%), and in formula (4), t is the retention time (s) at the soaking temperature, and Tdp is the dew point (° C.).
6. A method for manufacturing a component, comprising the step of subjecting the steel plate according to claim 1 or 2 to at least one of forming and joining to form a component.
Citation Information
Patent Citations
High-strength cold rolled steel sheet with excellent ductility and chemical conversion treatability, and its manufacturing method
JP2006083403A
Highly-processable high strength cold-rolled steel sheet excellent in chemical convertibility and method for manufacturing the same
JP2015113505A
Ultra-high strength steel sheet with excellent chemical conversion treatability and hole expandability, and its manufacturing method
JP2019502819A
Cold-rolled high-strength steel sheet with excellent phosphate treatability and formability and its manufacturing method
JP2019531408A
Steel sheet and method for producing same
WO2022138396A1